Client‐led care in HIV: perspectives from community and practice. (23rd July 2021) - Crawford, David; Allan, Brent; Cogle, Aaron; Brown, Graham
Abstract: Objectives: While current antiretroviral and care strategies can effectively suppress HIV, achieving optimal quality of life (QoL) requires a wider consideration of clients' well‐being, the complexity of individuals' lives and social determinants of health. The objective of this commentary was to develop a definition of client‐led care in the Australian context and its key supporting principles for people living with HIV (PLHIV). Methods: The authors used two sources of evidence to support their HIV community experience with client‐led care: (1) a scoping review of the literature, and (2) consultations with colleagues who were PLHIV advocates or HIV specialist physicians. The findings from the scoping review and consultations were summarised and the key principles of client‐led care compared with those identified by the authors. Results: Seven articles met the inclusion criteria for qualitative analysis in the scoping review. Five PLHIV advocates and three HIV specialist physicians were consulted. Key principles supporting client‐led care identified by the authors based on their experience centred around the themes of: (1) clients and healthcare providers working in partnership, (2) information and communication, (3) coordinating access to care, (4) building trust, and (5) respect for client's needs and preferences. The principles identified by the authors were supported by those of the scoping review and colleague consultations. Conclusions: A client‐led approach can complement conventional HIV care strategies and enable empowerment and greater engagement with care, potentially improving the care continuum and overall QoL for individuals living with HIV who can, and want to, lead their own care.